Analyzing factors influencing Vietnam,s garment exports to Germany using the SMART model - Pham Van Kiem; Pham Thi Nhan; Tran Quang Manh; Vu Hoang Le Minh; Pham Thi Minh Ngoc (Journal of State Management, 2025)
After more than three years of implementing the EU - Vietnam Free Trade Agreement (EVFTA), its effects on Vietnam's economy, particularly within the textile and garment sector, have become increasingly apparent. Analyzing the impact of the EVFTA on garment exports to Germany is critical, as Germany constitutes a significant and high-potential market for Vietnamese products. Utilizing the SMART model, the study indicates that the trade creation effect accounts for 64% of the total impact, while trade diversion effects contribute 36%. These findings underscore the competitive pricing advantage of Vietnamese garments compared to EU domestic products, driven by reduced export tariffs to 0% under the EVFTA. Based on the results, the authors propose some policy recommendations to optimize the agreement's benefits and further enhance the export performance of Vietnamese garments in the German market.